Relaxing dog: creating and testing non-vocal music in dog environments - Björklund, Anna (My University, 2022)
Sounds of different kinds have an impact on humans as well as on animals. Regarding animals, it is known that for example dogs can be negatively affected by fireworks on new years eve. Hence, the owners try to facilitate for their dog through putting cotton wool in their ears, providing them de-stressing pheromones or even taking them to an airport hotel to get rid of the frightening noises of that night. However, the stress is not always caused by sudden noises. A trip to the veterinary can cause stress to the animal due to sound-, sight- and scent impressions. Is it possible to add sound to ease the experience in this type of situation? This thesis work is a continuation of sound tests performed in dog environments. It overlaps the existing literature by testing classical music and expands the knowledge by also testing nature and ambient sounds with the aim to enhance dogs’ welfare. The purpose of this study is to investigate whether it is possible to use sound design as a tool for improving dog environments. The study is performed exploratively so that the assessors had a chance to provide feedback on the design of the forms. Direct observations were carried out in a dogs’ daycare and at a veterinary station. The data processing was a combination of quantitative and a small part qualitative analysis. The results are of varying character. However, two test sounds: ambient and classical, may have deactivating effects on some groups and individuals. Nature sound showed more activated behaviour in a majority of groups and individuals. Brayley & Montrose, (2016) and Bowman et al., (2017) supports the difficulties with certainty pointing out a universal genre or type of sound that would work deactivating on dogs in general. However, it is clear that individual preferences play an important role and that the variation itself can be a key to enhancing the welfare of dogs.
Keywords: Dog; stress, sound test, music test, welfare, heart rate, respiratory rate, veterinary station